Factors affecting construction productivity: a 30 year systematic review. Issue 7 (1st August 2018) - Hasan, Abid; Baroudi, Bassam; Elmualim, Abbas; Rameezdeen, Raufdeen
Abstract : Purpose: A significant amount of work has been performed in the area of identification of factors affecting construction productivity. Previous studies have tried to determine the most important factors affecting construction productivity in different countries for a long time. As a result of continuous effort in this direction, researchers have identified a wide range of factors. While the subject area has matured, no general agreement could be made on the factors affecting construction productivity. To fill this gap, the purpose of this paper is to undertake a comprehensive systematic review of mainstream studies on factors affecting construction productivity published in the last 30 years (1986–2016). Design/methodology/approach: A total of 46 articles from different sources such as journals, conference proceedings, dissertation and PhD theses were identified and thoroughly reviewed. Findings: Gaps in research and practices are discussed and directions for future research have been proposed. The literature review indicates that despite noticeable differences in the socio-economic conditions across both developed countries and developing countries, an overall reasonable consensus exists on few significant factors impeding productivity. These are, namely, non-availability of materials, inadequate supervision, skill shortage, lack of proper tools and equipment and incomplete drawing and specifications. Nevertheless, implications of technology, site amenities, process studies, project culture, and impacts of physiological and psychological factors were not adequately covered in existing literature. The study also found that traditional construction projects have remained the main focus of these studies while green construction projects have been generally overlooked. Research limitations/implications: The review does not include studies that report productivity at the organisational or industry level as well as total factor productivity. The scope of the review is limited to work on identification of factors affecting productivity at the activity level in construction projects. Practical implications: The outcomes of this study would help researchers and practitioners by providing the findings of previous studies in a concise manner. It is also expected that presenting a deeper and wider perspective of the research work performed until now will direct a more focussed approach on productivity improvement efforts in the construction industry. Originality/value: This review paper undertakes a comprehensive systematic review of studies on identification of factors affecting construction productivity published during the last three decades.